The Evidence of Crucifixion on the Shroud of Turin Through the Anatomical Traits of the Lower Limbs and Feet. (3rd May 2018) - Caja, V. L.; Boi, M.
Abstract : The imprint of the feet and lower limbs, as well as the blood and rivulets, present on the Shroud of Turin were analysed with regard to anatomical and pathological characteristics. In the dorsal image of the cloth, the crucifixion position shows the left foot on top of the right one; in the frontal view, the feet are almost parallel. The nail used in the crucifixion was driven through the foot. In the frontal image, the knees, the tibiae and the ankles seem to be parallel with different varus–valgus angles; the left one is straighter than the right one, which shows a greater angle. Because of this parallelism, both ankles show a plantar flexion that is dissimilar in the dorsal images. We describe for the first time the anatomical study of the image of the Shroud through modern concepts. At the level of biomechanics and anatomy, the image on the Shroud of Turin does not comply with modern knowledge; in fact, the image fails with regard to some aspects that we cannot interpret yet.